Anatomy of sugar apple (annona squamosa l.) seeds (annonaceae) (2013)
The sugar apple is of great economic importance to the country,however, information on the anatomical and morphologicalaspects of Annonaceae family seeds is limited to a few speciesand the anatomical studies refer to very few seeds. Using histologicaltechniques and microscopy, Annona squamosa L. seedswere studied with regard to their anatomical characteristics.In general, they presented the typical anatomical patterns ofseeds of the Annonaceae family. The multilayered testa wascomprised of exo-, meso- and endotestas, with the presenceof longitudinal and oblique fibers. The embryo was small andstraight with moderately developed embryonic axis, rudimentaryplumule and flat and thin cotyledons, wherein one couldobserve the procambium. In particular, the perichalaza wasobserved in the medium longitudinal plane of the endotestawith more than two rows of vascular tissue. The tegmen or innerintegument was collapsed. The micropylar plug was tapered,woody and composed of transverse fibers; a fracture line wasalso observed. The ruminate endosperm interfered with boththe inner and external integuments. Oleiferous idioblasts wereobserved at the outer edges of the ruminations.